The German House : a novel - Hess, Annette, 1967- (HarperVia, 2019)
"If everything your family told you was a lie, how far would you go to uncover the truth? For twenty-four-year-old Eva Bruhns, World War II is a foggy childhood memory. At the war's end, Frankfurt was a smoldering ruin, severely damaged by the Allied bombings. But that was two decades ago. Now it is 1963, and the city's streets, once cratered are smooth and paved. Shiny new stores replace scorched rubble. Eager for her wealthy suitor, Jurgen Schoormann, to propose, Eva dreams of starting a new life away from her parents and sister. But Eva's plans are turned upside down when a fiery investigator, David Miller, hires her as a translator for a war crimes trial. As she becomes more deeply involved in the Frankfurt Trials, Eva begins to question her family's silence on the war and her future. Why do her parents refuse to talk about what happened? What are they hiding? Does she really love Jurgen and will she be happy as a housewife? Though it means going against the wishes of her family and her lover, Eva, propelled by her own conscience, joins a team of fiery prosecutors determined to bring the Nazis to justice -a decision that will help change the present and the past of her nation."--Publisher description.